HUBUNGAN BERAT BADAN LAHIR DAN MASA GESTASI DENGAN TUMBUH KEMBANG PADA BALITA DI POSYANDU DESA SUNGAI LALA - Putri Wulandini; Yulia Febrianita; Rostia Febriani; Andalia Roza (JOMIS (Journal of Midwifery Science), 2024)
Birth Weight (BBL) is the weight measured within the first hour after birth, normally 2.500-4.000 grams. The gestation period is defined as the period of pregnancy starting from conception until birth of the fetus. The toddler years are a period of very rapid and critical growth, usually known as the golden age. The aim of the research was to determine the relationship between Birth Weight (BBL) and gestation period with growth and development in toddlers at Posyandu Titi Harum, Sungai Lala Village. This type of research is quantitative with a correlational approach. This research was carried out at Posyandu Titi Harum and Kasih Ibu, Sungai Lala Village. In November 2023. The population in this study was 95 respondents using a total sampling technique. Bivariate data analysis technique, data collection method using the KPsp questionnaire sheet. The results showed that toddlers in the normal BBL category (67,37%), abnormal BBL (32,63%), premature (25,26%), not premature (74,74%), had appropiate growth and development (67,37%) and not appropriate (32,63%). The results of the chi-square test obtained a p-value = 0,001 which shws that there is a significant between birth weight and gestation period and the growth and development of toddlers at Posyandu Titi Harum and Kasih Ibu Sungai Lala Village in. It is hoped that monitoring of growth and development will be further improved through routine early detection of deviations in children.